Odpowiedzi

2012-08-04T15:08:56+02:00

a)

p=x+4    ;    q=\frac{1}{2}x+1

p^2-q^2=\\=(x+4)^2-(\frac{1}{2}x+1)^2=\\=x^2+8x+16-(\frac{1}{4}x^2+x+1)=\\=x^2+8x+16-\frac{1}{4}x^2-x-1=\\=\frac{3}{4}x^2+7x+15

 

p>q\\ x+4>\frac{1}{2}x+1\\ \frac{1}{2}x>-3\ |*2\\ x>-6

 

D=(-6;∞)

 

b)

p=x^2+x      ;    q=2x-2

p^2-q^2=(x^2+x)^2-(2x-2)^2=\\=x^4+2x^3+x^2-(4x^2-8x+4)=\\=x^4+2x^3+x^2-4x^2+8x-4=\\=x^4+2x^3-3x^2+8x-4

 

p>q\\ x^2+x>2x-2\\ x^2-x+2>0\\

Δ=(-1)^2-4*1*2=1-8=-7

 

D={R}

2012-08-04T15:17:19+02:00